A Simple Synthesis of 2‐(Arylmethylidene)hydrazinylidene]‐3‐hydroxy‐4H‐furo[3, 2‐c]pyran‐4(3H)‐ones. Issue 4 (10th April 2013) - Adib, Mehdi; Ansari, Samira; Zhu, Long‐Guan; Rahimi‐Nasrabadi, Mehdi
Abstract A simple synthesis of 2‐hydrazinylidene‐3‐hydroxy‐4H‐furo[3, 2‐c]pyran‐4‐ones is described. A mixture of (isocyanoimino)(triphenyl)phosphorane, an aromatic aldehyde, and dehydroacetic acid (=3‐acetyl‐2‐hydroxy‐6‐methyl‐4H‐pyran‐4‐one) undergo a 1 : 1 : 1 addition reaction under mild conditions to afford the title compounds in excellent yields.